Preparation of KI/KIO3/Methoxide Kaolin Catalyst and Performance Test of Catalysis in Biodiesel Production - Buchori, Luqman; Widayat; Ngadi, Norzita; Hadiyanto; Okvitarini, Ndaru (Science and Technology Indonesia, 2024)
Kaolin is a natural ingredient that is in abundance and has not been widely used. Kaolin is a source of silica (SiO2) and alumina (Al2O3) so that it can be used as a heterogeneous catalyst in biodiesel production. This research aims to examine the influence of using impregnated kaolin as a heterogeneous catalyst on production of biodiesel. Research methods include calcination of natural kaolin, impregnation of kaolin using KI, KIO3, and preparation of kaolin-methoxide in various concentrations, as well as biodiesel production using an impregnated kaolin catalyst. The catalyst was characterized using XRD and SEM. The catalyst was tested for basicity using the Hammet indicator method with acid-base titration. The biodiesel product obtained was analyzed using GCMS. The results of XRD analysis showed that 8% kaolin-methoxide catalyst had the highest crystallinity among the others. The crystallinity obtained was 87.84% with a composition of 15.79% SiO2 and 78.86% Al2O3. SEM image results also show a more visible crystal shape. The highest basicity of the catalyst obtained was 0.240 mmol. The highest biodiesel yield using 8% kaolin-methoxide catalyst is 99.48%.